Excluded volume effects caused by high concentration addition of acid generators in chemically amplified resists used for extreme ultraviolet lithography. (3rd July 2017) - Kozawa, Takahiro; Watanabe, Kyoko; Matsuoka, Kyoko; Yamamoto, Hiroki; Komuro, Yoshitaka; Kawana, Daisuke; Yamazaki, Akiyoshi
Abstract: The resolution of lithography used for the high-volume production of semiconductor devices has been improved to meet the market demands for highly integrated circuits. With the reduction in feature size, the molecular size becomes non-negligible in the resist material design. In this study, the excluded volume effects caused by adding high-concentration acid generators were investigated for triphenylsulfonium nonaflate. The resist film density was measured by X-ray diffractometry. The dependences of absorption coefficient and protected unit concentration on acid generator weight ratio were calculated from the measured film density. Using these values, the effects on the decomposition yield of acid generators, the protected unit fluctuation, and the line edge roughness (LER) were evaluated by simulation on the basis of sensitization and reaction mechanisms of chemically amplified extreme ultraviolet resists. The positive effects of the increase in acid generator weight ratio on LER were predominant below the acid generator weight ratio of 0.3, while the negative effects became equivalent to the positive effects above the acid generator weight ratio of 0.3 owing to the excluded volume effects.